ANALISIS PENGARUH INTERAKSI ENGINE PROPELLER MATCHING DALAM MENGOPTIMALISASIKAN PERFORMA PENGGERAK KAPAL IKAN - Pardi; Maful Suranto; Afriantoni; Abdul Halim; Nur Hafizah Khansa; Sapta Pradana Atfi (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
With the rapid advancement of science and technology, fishing vessels have experienced significant development, particularly in their propulsion systems. This study addresses the selection of an effective and efficient propulsion system for a previously developed fishing vessel, with principal dimensions of Lpp = 7.798 m, B = 1.575 m, H = 0.678 m, T = 0.4 m, and a block coefficient (Cb) of 0.449. In operation, vessel speed is a crucial factor that greatly affects the effectiveness and success of fishing activities. Fishermen are required to reach fishing grounds as quickly as possible, especially under conditions influenced by tidal currents and the dynamic movement of fish schools. Therefore, an analysis of the propulsion system is essential to improve the performance of fishing vessels. To analyze performance, simulations were conducted using Computational Fluid Dynamics (CFD). Based on the simulation results, a resistance force of 1865 N at a speed of 10 knots requires an engine power of 28 HP. This performance was achieved using a DongFeng S1125 engine coupled with a B3-80 type propeller with a diameter of 0.34 meters.